Equity, walkability, and active school transportation in Toronto, Canada: A cross-sectional study. (July 2022) - Kunaratnam, Vijayagovry; Schwartz, Naomi; Howard, Andrew; Mitra, Raktim; Saunders, Natasha; Cloutier, Marie-Soleil; Macpherson, Alison; Fuselli, Pamela; Rothman, Linda
Highlights: Neighbourhood proportion of recent immigrants is associated with more walking to school. Social factors appear to have stronger associations with active school transportation in less walkable environments. Social factors must be considered when promoting active school travel, accounting for inequities and community knowledge. Abstract: Active school transportation (AST) benefits children's health. Social factors, including low-income, visible minority status, and immigration have been associated with more AST. However, the mechanism by which they influence AST is not well understood, nor is their interaction with built environment features. This cross-sectional study examined associations between area-level social factors (material deprivation, ethnic concentration, proportion recent immigrants, proportion visible minority), and AST across 105 elementary schools in Toronto, Canada, controlling for multi-dwelling density and Walk Score®. A significant association between proportion recent immigrants and AST was found in adjusted analyses (OR = 1.54, 95 %CI:1.14–2.07, per 10% increase). No significant association was found with other social factors. In analyzing effect modification, social factors appeared to have stronger associations with AST in less walkable environments. This analysis indicates that the influence of the built environment varies across social factors, suggesting the need to account for equity when promoting active travel to school.